Psychological review. - Baldwin, James Mark 1861-1934; Cattell, James McKeen 1860-1944; Warren, Howard C. 1867-1934 (Howard Crosby).; Watson, John B. 1878-1958 (John Broadus).; Langfeld, Herbert Sidney 1879-; Pratt, Carroll C. 1894- (Carroll Cornelius).; Newcomb, Theodore Mead 1903-; American Psychological Association (Washington American Psychological Association)
Issues for 1894-1903 include the section: Psychological literature.
At head of title, v. 17-44: Psychological review publications.
Editors: 1894-1903, J. M. Baldwin, J. M. Cattell; 1904-Jan. 1910, J. M. Baldwin, H. C. Warren and others; Mar. 1910-May 1927, H. C. Warren, J. B. Watson and others; July 1927-July 1934, H. C. Warren; Sept. 1934-Nov. 1947, H. S. Langfeld; 1948-53, C. C. Pratt; 1954- T. M. Newcomb.
Keywords: Psychology -- Periodicals